Atrial fibrillation and venous thromboembolism: evidence of bidirectionality in the Atherosclerosis Risk in Communities Study. (13th March 2018) - Lutsey, P. L.; Norby, F. L.; Alonso, A.; Cushman, M.; Chen, L. Y.; Michos, E. D.; Folsom, A. R.
Abstract : Essentials Atrial fibrillation (AF) may increase risk of venous thromboembolism (VTE), and vice versa. Bidirectionality was assessed prospectively via data from 15 129 black and white individuals. AF was associated with greater risk of developing VTE, and VTE with greater risk of AF. Associations were strongest among blacks and in the first 6 months after initial diagnosis. Summary: Background: Atrial fibrillation (AF) and venous thromboembolism (VTE) frequently co‐occur. These conditions have shared risk factors and are accompanied by coagulation abnormalities. Furthermore, mechanistic pathways may directly link the disorders. Objectives: To test the hypothesis that individuals with incident AF are at greater risk of developing VTE, and those with VTE are at elevated risk of AF. We also tested whether associations were stronger in the first 6 months after the initial diagnosis, and explored race differences. Patients/Methods: A total of 15 129 ARIC study participants (45–64 years, 55% female, 26% Black) were followed from 1987 to 2011 for incident AF and VTE (median follow‐up 19.8 years). Multivariable‐adjusted Cox regression was used, with AF and VTE modeled as time‐dependent exposures. Results: Incident AF was associated with greater risk of subsequent incident VTE (hazard ratio [95% CI], 1.71 [1.32–2.22]); the association was stronger in Black people (2.30 [1.48–3.58]) and during the first 6 months after AF diagnosis (5.08 [3.08–8.38]). Similarly, incident VTE was associated with increased risk of incident AF (1.73 [1.34–2.24]), especially in Black people (2.40 [1.55–3.74]) and in the first 6 months after VTE diagnosis (4.50 [2.61–7.77]). Conclusions: The occurrence of AF was associated with increased risk of incident VTE, and occurrence of VTE was associated with greater risk of incident AF. Associations were particularly strong among Black people and during the first 6 months after the initial diagnosis, although they remained elevated even after 6 months. These findings highlight patient populations that may be at increased risk of AF and VTE, and perhaps should be targeted with preventive strategies.